Revocation of Citizenship and Rule of Law: How Judicial Review Defeated Britain's First Denaturalization Regime. (10th May 2018) - Weil, Patrick; Handler, Nicholas
Abstract : Over the past decade, the United Kingdom has deprived an increasing number of British subjects of their citizenship. This policy, known as "denaturalization, " has been applied with particular harshness in cases where foreign-born subjects have been accused of terrorist activity. The increase is part of a global trend. In recent years, Canada, Australia, France, and the Netherlands have either debated or enacted denaturalization statutes. But Britain remains an outlier among Western democracies. Since 2006, the United Kingdom home secretary has revoked the citizenship of at least 373 Britons, of whom at least 53 have had alleged links to terrorism. This is more than the total number of revocations by Canada, France, Australia, and Netherlands combined. These developments are troubling, as the right to be secure in one's citizenship has been a cornerstone of the postwar European liberal political order, and of the international community's commitment to human rights.